Evaluation of hypertension in systemic sclerosis and systemic lupus erythematosus overlap. Issue 1 (February 2023) - Chew, Erin; Barnado, April; Ikizler, Talat Alp; Zent, Roy; Frech, Tracy
Patients with systemic sclerosis and systemic lupus erythematosus serologies present a unique challenge to the clinician when hypertension is detected in the outpatient setting. Treatment choices for non-renal crisis hypertension are different for systemic sclerosis versus systemic lupus erythematosus. Urgent laboratory studies and, in the presence of certain symptoms, imaging assessment are indicated in systemic sclerosis and systemic lupus erythematosus overlap patients with systemic hypertension. Long-term assessment of systemic hypertension may be enhanced by advances in non-contrast imaging that serve as valuable biomarkers for progressive vasculopathy. In this review, the diagnostic approach to systemic sclerosis and systemic lupus erythematosus overlap patients presenting with hypertension is discussed.